2017
DOI: 10.1152/physiolgenomics.00006.2017
|View full text |Cite
|
Sign up to set email alerts
|

Cancer cachexia-induced muscle atrophy: evidence for alterations in microRNAs important for muscle size

Abstract: Muscle atrophy is a hallmark of cancer cachexia resulting in impaired function and quality of life and cachexia is the immediate cause of death for 20-40% of cancer patients. Multiple microRNAs (miRNAs) have been identified as being involved in muscle development and atrophy; however, less is known specifically on miRNAs in cancer cachexia. The purpose of this investigation was to examine the miRNA profile of skeletal muscle atrophy induced by cancer cachexia to uncover potential miRNAs involved with this cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 41 publications
1
65
0
1
Order By: Relevance
“…Excessive protein degradation is the main cause for skeletal muscle atrophy, which is harmful to human health and leads to muscle fatigue and reduced life span (28)(29)(30)(31). Abnormal protein degradation and muscle atrophy generally occur with genetic mutation (DMD) (32), hormone exposure (glucocorticoid) (33), or disease (cachexia) (34). Many studies have shown that appropriate exercise can induce muscle hypertrophy and is also an effective way to rescue muscle atrophy (35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…Excessive protein degradation is the main cause for skeletal muscle atrophy, which is harmful to human health and leads to muscle fatigue and reduced life span (28)(29)(30)(31). Abnormal protein degradation and muscle atrophy generally occur with genetic mutation (DMD) (32), hormone exposure (glucocorticoid) (33), or disease (cachexia) (34). Many studies have shown that appropriate exercise can induce muscle hypertrophy and is also an effective way to rescue muscle atrophy (35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…It would be also important to assess intramuscular Ucp1 expression in other models of atrophy. This will, however, likely require experiments with additional animal species because fatty infiltration is generally not observed during denervation atrophy [66][67][68][69] or cancer cachexia 65,[70][71][72] in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic inflammation has been reported in the majority of patients with CAC and causes disruption of morphofunctional aspects of many tissues, such as the brain, the adipose tissue, and the muscle, while also affecting tumour biology . The secretory profile of the tumour may be associated with cachexia–muscle wasting, as proposed by de Matos‐Neto et al .…”
Section: Introductionmentioning
confidence: 92%
“…3 Clinically, CAC consists of chronic systemic inflammation and catabolism, leading to reduction of quality of life, diminished treatment tolerance, tumour metabolic reprograming, and, consequently, decreased survival. [4][5][6] Chronic inflammation has been reported in the majority of patients with CAC 7 and causes disruption of morphofunctional aspects of many tissues, such as the brain, 8,9 the adipose tissue, [10][11][12][13] and the muscle, 14,15 while also affecting tumour biology. 5,16 The secretory profile of the tumour may be associated with cachexia-muscle wasting, as proposed by de Matos-Neto et al.…”
Section: Introductionmentioning
confidence: 99%